Student Thinking Process in Solving Mathematical Representation Problems - Alfiah Nurfadhilah AM. Hindi; Iwan Setiawan HR (Department of Mathematics Education University of Muhammadiyah Malang, 2023)
This research was qualitative research with descriptive approach, which aimed determined the level of success of students in solving representation problems based on the type of representation, namely numbers, algebra, geometry, and statistics and to know their thinking processes. The subjects of this study were first semester students at Patompo University who were selected using a purposive sampling technique. The subjects of this study were 2 students in each representational domain. Data were analyzed to determine the results of problem solving and students' thinking processes in solving representation problems in mathematics. Based on the results of the research on solving visual representation problems based on TRM-01 and TRM-02, most of the students failed especially in algebraic material which was caused by difficulties in solving representation problems. This is shown based on the percentage of students' success in solving representation questions.